Peraturan Daerah Bermuatan Syariat Islam Ditinjau Dari Prinsip Demokrasi Konstitusional - Fuqoha, Fuqoha (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
Abstract: In managing a local government or municipality, regulation is a must. Forms of regulatory framework in this context is bylaw. In today’s democratic Indonesia, local government has authority to form and implement bylaw according to local needs and values. Including bylaw on sharia. Among the purpose of bylaw is maintaining order. From the perspective of constitutional democracy, sharia bylaws is the right of each local government and community as long as not contradictory to the Constitution. Liberty to enact certain bylaw shows a working democracy. Therefore, sharia bylaw is an indication of ideal democracy, not threat to democracy. Key Words: bylaws, sharia, constitutional democracy